[tex]u_{n+1}=\frac{1}{3}(\frac{n+1}{n})u_{n}\Rightarrow \frac{u_{n+1}}{n+1}=\frac{1}{3}.\frac{u_{n}}{n}[/tex]
Đặt [tex]v_{n}=\frac{u_{n}}{n}\Rightarrow \left\{\begin{matrix} v_{1}=1 & \\ v_{n+1}=\frac{1}{3}v_{n}& \end{matrix}\right.[/tex]
[tex]\Rightarrow v_{n}[/tex] là CSN với công bội [tex]\frac{1}{3}\Rightarrow v_{n}=v_{1}.\left ( \frac{1}{3} \right )^{n-1}=\left ( \frac{1}{3} \right )^{n-1}[/tex]
[tex]\Rightarrow u_{n}=n.v_{n}=n.\left ( \frac{1}{3} \right )^{n-1}[/tex]
[tex]S_{n}=\sum \frac{u_{n}}{n}=\sum \left ( \frac{1}{3} \right )^{n-1}[/tex] [tex]=\frac{1-\left ( \frac{1}{3} \right )^{n}}{1-\frac{1}{3}}=\frac{3}{2}-\frac{3}{2}.\left ( \frac{1}{3} \right )^{n}[/tex] (công thức tổng cấp số nhân)
[tex]\Rightarrow lim(S_{n})=lim(\frac{3}{2}-\frac{3}{2}.\left ( \frac{1}{3} \right )^{n})=\frac{3}{2}-0=\frac{3}{2}[/tex]